Testing Environmental Kuznets Curve Hypothesis in Somalia: Empirical Evidence from ARDL Technique - Hussein, Hassan Abdikadir; Warsame, Abdimalik Ali (International Journal of Energy Economics and Policy, 2023)
Economic growth is typically attributed as the fundamental cause of environmental problems due to higher production which generates more pollution. The EKC hypothesis is used to test the link between economic growth and environmental pollution. In this regard, this study aims to ascertain the validity of the EKC hypothesis in Somalia using time series data spanning between 1989 to 2020. The autoregressive distributed lag (ARDL) technique is applied to verify the presence of EKC and integrations between the sampled variables. According to the empirical result, it was revealed that all the regressors are statistically significant except trade openness. Agriculture production and squared economic growth are negatively related to environmental pollution whereas economic growth significantly impedes environmental quality in Somalia. Hence, an inverted U-shaped relation between growth and pollution has been found confirming the EKC hypothesis. In contrast, both economic growth and squared growth Granger cause environmental pollution but not vice versa. Policymakers should develop environmental policies to help reduce pollution emissions in order to achieve economic sustainability in the country by promoting and investing in cleaner energy resources to improve Somalia’s economy’s overall energy efficiency.